Detection and analysis of power quality disturbances using bilinear time-frequency distribution / Wan Mohammad Faiz Wan Sharifudin - Wan Sharifudin, Wan Mohammad Faiz (2013)
Power Quality (PQ) is the most prolific and major concern in power industry especially for the power engineers, respectively. Maintaining the power quality at high level is always the aim for the power engineers so that the power delivered efficiently with lesser power loss. Voltage, current or frequency deviation manifesting in the power quality problem would result in failure or permanent disoperation of apparatus and load equipments. Time Frequency Distribution (TFD) is a powerful tool that have attract interest of many power engineering researchers to be tested for recognition and detection of power quality (PQ) disturbances with power related analysis. The development of TFD has been progressively studied under Digital Signal Processing field and it have been used to analyze various real-lite problems such as radar, sonar, seismic data analysis, biomedical engineering, and automatic emission. The method used in this study is Wigner Ville Distribution, This method would introduce power quality distortion signal representation in term of bilinear Time-Frequency Representation (TFR) Representation of analysis in classical time or frequency only is not sufficient to show further characteristic and information carried by the signal. Therefore by combining both time and frequency the analysis could be extended to further level such as energy density.